Грошові податі та збори у Наддіпрянській Україні наприкінці XVIII – на початку ХХ ст.: сучасний науковий дискурс - Домнін, Д.; Domnin, D. (ЦНТУ, 2025)
У статті здійснено історіографічний аналіз досліджень грошових податей і зборів у Наддніпрянській Україні XVIII – початку XX ст., розкрито основні напрями наукового осмислення податкової політики російської імперії щодо українських земель. Визначено ступінь розробленості проблеми в сучасній українській історіографії, окреслено дискусійні питання та наголошено на необхідності комплексного вивчення грошового оподаткування в контексті соціально-економічної та історико-антропологічної перспективи. The article provides a historiographical analysis of studies on monetary taxes and levies in Nadiprian Ukraine in the 18th – early 20th centuries, revealing the main directions of scientific understanding of the russian Empire's tax policy towards Ukrainian lands. It determines the degree of development of the problem in contemporary Ukrainian historiography, outlines controversial issues, and emphasises the need for a comprehensive study of monetary taxation in the context of socio-economic and historical-anthropological perspectives.
Money taxes and fees in Nadiprian Ukraine at the end of the 18th – early 20th centuries: modern scientific discussion
Keywords: грошові податі; подушне оподаткування; Наддніпрянська Україна; історіографія; monetary taxes; poll tax; Nadiprian Ukraine; historiography